Effectiveness of Dobutamine to Facilitate Induction of Supraventricular Tachycardia Compared to Isoproterenol - Donnelly, Joseph; Rahyab, Ali Seyar; Ismail, Haisam; Epstein, Laurence; Goldner, Bruce (Cardiology and Cardiovascular Medicine, 2023)
Background: Isoproterenol has been utilized for the induction of supraventricular and ventricular arrhythmias during electrophysiological (EP) testing. However, with the increasing number of catheter ablations performed and the significant increase in the price of isoproterenol in 2015, the cost implications led us to explore alternatives, although the price of isoproterenol has decreased since 2015. Dobutamine is a synthetic compound which was developed from isoproterenol with a similar ability to enhance conduction and shorten refractoriness of the AV node, thus making it an ideal choice given its lower cost. The effectiveness of dobutamine to facilitate induction of arrhythmias has not been extensively studied. Objective: To evaluate the ability of dobutamine to reproduce the properties of isoproterenol to help facilitate induction of arrhythmias. This study also evaluated the safety of dobutamine. Methods: From January 2014 to January 2017, 174 non-consecutive patients, with a diagnosis of confirmed or suspected supraventricular tachycardia (SVT) were enrolled. Dobutamine was used to induce SVT if patients were non-inducible at baseline using programmed electrical stimulation (PES). Post procedure, dobutamine was used to confirm noninducibility. Data such as demographics, comorbidities, and recurrence of arrhythmia were collected. The procedural end point was confirmation of non-inducible SVT. A different cohort of twenty non-consecutive patients, who received isoproterenol to facilitate induction of SVT, were evaluated in this study commensurate when dobutamine was being used in the other cohort of patients. Twenty patients who received 10, 20 and 30 mcg/kg/min of dobutamine and 10 patients who received 1 and 2 ug/min of isoproterenol were selected to study the electrophysiologic effects of escalating doses of these medications. Results: Sixty-seven of 172 patients (39%) did not require pharmacologic intervention to induce AT, AVNRT or AFL. Of the 105 remaining patients, 85 patients received dobutamine to induce AT, AVNRT or AFL and 20 patients received isoproterenol. Overall, there was no difference in inducibility of SVT and atrial flutter with PES and dobutamine compared with PES and isoproterenol. However, when SVT inducibility was evaluated alone without atrial flutter inducibility, dobutamine with PES induced 94% of patients whereas isoproterenol with PES induced 80%, p = 0.03. Sustained polymorphic ventricular tachycardia occurred in 3.5% of dobutamine plus PES cases compared with 5% of isoproterenol plus PES cases. There was no difference in the rate of recurrence of SVT and atrial flutter whether dobutamine or isoproterenol was used. Conclusion: This study supports the use of dobutamine as an adjunct to electrophysiologic study of patients with SVT and atrial flutter both for the induction of SVT and assessment of procedural success. In our study dobutamine was safe and effective.